1997
DOI: 10.1128/iai.65.8.3203-3208.1997
|View full text |Cite
|
Sign up to set email alerts
|

Neisserial porins may provide critical second signals to polysaccharide-activated murine B cells for induction of immunoglobulin secretion

Abstract: Resting B cells stimulated with dextran-conjugated anti-immunoglobulin D (anti-IgD) antibodies (anti-Igdex), a model for B-cell activation in response to polysaccharide antigens, proliferate but secrete little if any Ig, unless additional stimuli are present. In order to elucidate the parameters which costimulate T-cellindependent antipolysaccharide antibody responses during bacterial infections, we tested the capacities of highly purified porin proteins from Neisseria meningitidis and Neisseria gonorrhoeae to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…These proteins, which serve as molecular sieves on the surfaces of a number of gram-negative bacteria such as Neisseria meningitidis and Salmonella typhimurium (120), can stimulate B-cell expression of co-stimulatory B7.2 molecules, proliferation and Ig secretion (121,122). We have observed synergy between ad-dex and three purified neisserial porins in IgM induction that was similar to the synergy of ad-dex with LPS, but did not require TLR4 expression (117).…”
Section: Microbial Products Provide Second Signals To B Cells Activatmentioning
confidence: 75%
“…These proteins, which serve as molecular sieves on the surfaces of a number of gram-negative bacteria such as Neisseria meningitidis and Salmonella typhimurium (120), can stimulate B-cell expression of co-stimulatory B7.2 molecules, proliferation and Ig secretion (121,122). We have observed synergy between ad-dex and three purified neisserial porins in IgM induction that was similar to the synergy of ad-dex with LPS, but did not require TLR4 expression (117).…”
Section: Microbial Products Provide Second Signals To B Cells Activatmentioning
confidence: 75%
“…B7-2 is involved in costimulation during B cell^T cell interactions. A subsequent study demonstrated a synergistic e¡ect of neisserial porins with CD40 ligand which is expressed in activated T cells [10]. Taken together, these data suggest a physiological role for porins in augmenting T cell participation on the immune response to Neisseria.…”
Section: Introductionmentioning
confidence: 82%
“…This NK T-cell expansion occurs within a similar time frame to the MZ-derived plasmablast wave. The expansions of both cell types may be induced by non-protein components of bacteria cell walls, such as Gram-negative-derived mitogens including LPS as well as newly described mitogens from Grampositive bacteria and glycolipids presented by CD1 (84)(85)(86).…”
Section: Functional Traits Of Mz B Cellsmentioning
confidence: 99%